Krisis Keteladanan Kepemimpinan Gereja: Fondasi Gembala Sebagai Pemimpin Gereja Berdasarkan 1 Petrus 5:2-4 - Djone Georges Nicolas; Tirza Manaroinsong (Syntax Idea, 2021)
President Jokowi as the supreme leader of the Republic of Indonesia on January 13, 2021, has set an example and at the same time proved his promise to make himself the first person to be injected with the Covid-19 Sinovac vaccine. Pastor leadership which is basically aimed at serving, caring for and fulfilling the needs of the congregation as sheep that have been entrusted by God is shifting direction and starting to lose its meaning. Because leadership has begun to be used as a leader's "prestige" and a means to gain personal gain, so that pastoral leadership is no longer seen as a trust and mandate from God, but becomes a demand to be served and ignores the role models that are the responsibility of those they lead. It is no longer a blessing, but a stumbling block instead. This study uses descriptive qualitative methods and literature analysis, with the aim of analyzing the crisis of exemplary church leadership and the role of the pastor as church leader based on 1 Peter 5: 2-4. Collecting data through sources of books, journals, interviews, digital articles, and other documents related to the issues being studied. The results of the research are: First, pastors as church leaders need to realize that their leadership is a trust and a mandate from God. Second, the leadership quality of pastors must be superior to leadership in general by providing an example through volunteerism and self-dedication in serving the congregation they lead. Third, there is eternal reward for the shepherd who leads by example.